Pengaruh Budaya Dan Religiusitas Terhadap Keputusan Akuntan - Nisa Umahmudah A; Sany Dwita; Nayang Helma Yunita (Jurnal Eksplorasi Akuntansi, 2019)
This study aims to test empirically about: 1) The influence of culture on the accountant's decision, and 2) the influence of religiousity effect on the accountant's decision. This type of research belongs to a quasi experiment. Data in this study were collected by using questionnaires on 200 accounting students from 2 universities in Padang City and 1 university in Madura. Data analysis was done by using two-way ANOVA. The results of this study conclude that culture affects an accountant in decision making, while religiousity does not affect the accountant's decision. This study focuses on Javanese culture and Minangkabau culture with a construal of self approach in assessing accountant decisions and using accounting students as a subject to examine cultural and religiousity influences on professional accountant decisions.